PENJATUHAN PIDANA BERSYARAT DALAM TINDAK PIDANA LINGKUNGAN HIDUP (STUDI PUTUSAN NO. 319/PID/B/2013/PN.BB) - Meilisa Bangun; Alvi Syahrin; Syamsul Arifin; Suhaidi Suhaidi (USU LAW JOURNAL, 2017)
ABSTRACT   The implementation of probation does not apply solely on individual legal subject but also on corporate/ business entity as referred to in Verdict No. 319/Pid. B/2013/Pn. BB where the Defendant Lee Jong Hoan a.k.a Mr. Lee which categorized as the person who give order to proceed or the person who acted as the leader of the waste dumping activity to the environmental media without any permit. For the abovementioned action, Lee Jong Hoan a.k.a Mr. Lee is sentenced imprisonment for 10 (ten) months and do not have to undergo the imprisonment unless Lee Jong Hoan a.k.a Mr. Lee re-commit any criminal action before the probation period ends. The probation period applies for 1 (one) year, and sentenced Lee Jong Hoan a.k.a Mr. Lee to pay fine with the amount of IDR 5,000,00 (five million rupiah). The result of this research is that the provision regarding probation is not regulated in the Environmental regulation, but only in the KUHP. The sentence of conditional criminal charge in Verdict No. 319/Pid. B/ 2013/Pn. BB is not suitable because the act that the defendant committed is categorized as crime and the violation of environmental right, the penalty which was given to the defendant should be added to one-third because the defendant was the person who give order  to commit the criminal activity. The sentence of probation in environmental crime should refer to KUHP. Keywords: Probation, Environmental Crime.